PERFORMANCE OF COMMUNAL SANITATION FACILITY USING COMBINATION OF BIODIGESTER-BIOFILTER AND WASTE BANK FOR DOMESTIC WASTE TREATMENT - Darwati, Sri; Hastuti, Elis; Nuraeni, Reni (MATTER: International Journal of Science and Technology, 2019)
Most of slum settlements in the watershed areas have limited access to proper solid waste and wastewater management. Public sanitation facility is an integrated sanitation option in such area for solid waste treatment and wastewater treatment. The sanitation model has applied through the approach of community development, energy recovery and water reuse for agricultural area. The technology applied are biodigester and biofilter system for organic waste which mixed with black waste water, and waste bank for an organic waste management. The aim of this paper is to study performance and community development process of biodigester- biofilter system and waste bank in public sanitation facility. The study location took place at Lija Village, Megamendung District, Bogor City, West Java, Indonesia. Field research method of performance of domestic waste treatment and community based management were applied. Data analysis done through quantitative and qualitative descriptive method. The domestic waste treatment system consists of biodigester-biofilter system and waste bank. The main factors that affect the integrated management, is the level of education, awareness of healthy living and a willingness to manage the technology. The domestic waste that is generally vegetables and fruit with a composition of more than 50% mixed with black water in biodigester. The performance of biodigester- biofilter technology showed that BOD of treated water meet water reuse standard and the gas produced of 60-65% methane. Some challenges and obstacles in waste bank practice create fluctuation management condition and need routine monitoring from waste stakeholders to keep the sustainability.